A Descriptive Study on the Implementation of the Whole Word Approach to Improve Students' Vocabulary at Aura Sukma Insani Bilingual Kindergarten - ., Ni Komang Ayu Tri Purwanti; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Luh Diah Surya Adnyani, S.Pd. (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Bahasa Inggris sangatlah penting karena Bahasa Inggris adalah Bahasa yang paling umum diucapkan dimana saja. Bahasa Inggris digunakan dalam berkomunikasi di seluruh dunia. Bahasa Inggris juga diucapkan sebagai bahasa internasional dan Bahasa Inggris telah menjadi bahasa terpenting di seluruh bagian dunia, seperti di Bali. Untuk menguasai beberapa dasar pemahaman Bahasa Inggris lebih baik belajar Bahasa Inggris sejak usia dini. Namun, terdapat masalah dalam pengembangan kosa kata siswa di sekolah. Penguasaan kosa kata masih tetap rendah. Itu berarti bahwa kemampuan siswa dalam penguasaan kosa kata tidaklah optimal. Maka dari itu, penelitian ini bertujuan untuk mendeskripsikan tentang pengimplementasian the whole word approach untuk meningkatkan pencapaian kosata kata siswa di TK Bilingual Aura Sukma Insani. The whole word approach dapat diimplementasikan dengan banyak aktivitas yang menyenangkan dan menggembirakan. Aktivitas-aktivitas tersebut telah meningkatkan pencapaian kosa kata siswa secara efektif. Penelitian ini adalah penelitian kualitatif yang mana dilaksanakan terhadap siswa kelas B (5-6 tahun) di TK Bilingual Aura Sukma Insani. Subjek dari penelitian ini adalah siswa TK, guru-guru, and kepala sekolah TK Bilingual Aura Sukma Insani. Penelitian dikumpulkan dengan dua metode, diantaranya metode observasi dan metode interview.Kata Kunci : Whole word approach, Pencapaian kosa kata English is very important since English is the most common language spoken everywhere. It is widely used in communicating around the world, also it is spoken as an international language and it has become the most important language to many parts of the world, such as in Bali. In order to acquire some basics understanding it is better to study English from early age. However, there is problems in developing the student's vocabulary in the school. The mastery of vocabulary is still low. It means that, the student's ability is not optimal in mastering the vocabulary. This study is therefore, intended to describe about the implementation of the whole word approach for teaching students’ vocabulary achievement at Aura Sukma Insani Bilingual Kindergarten. The whole word approach could be implemented with so many fun and enjoyable activities. Those activities effectively improved students’ vocabulary achievement. This was a qualitative descriptive study which was conducted toward the B Class (age 5-6) in Aura Sukma Insani Bilingual Kindergarten. The subjects of this study were the kindergarten students, the teachers and principal of Aura Sukma Insani Kindergarten. This study was collected by two methods, such as observation method and interview method.keyword : whole word approach, vocabulary achievement